ANALYSIS OF EFFECTIVE COMPETITIVE ACTIVITY IN FRENCH SAVAT BOXING (Physical Culture and Sport: Scientific Perspective, 2025)
French boxing savate is a synthesis of martial arts that combines striking techniques with hands and feet. As a modern martial art, savate is still a relatively young sport that emerged due to the integration of the most effective technical and tactical techniques and training methods from various types of martial arts and martial arts. When considering French boxing savate, it is worth considering the methods of training athletes used in the most recognized martial arts in the world.Modern martial arts combine the best technical elements and means of tactical combat from sports that are close in technical and tactical arsenal, which makes it possible to apply a single methodological approach to their research. Analysis of competitive activity in savate shows a steady trend towards the growth of sports competition. Since the path to increasing training loads has natural limitations, the search for new approaches to improving the training process is relevant.Analysis of the effectiveness of defensive actions shows that savate players most often use defense by deflecting or moving back. This may be due to the predominance of the psychological factor, when the instinct of self-preservation plays a key role in choosing a method of defense.In French boxing savate, special attention should be paid to defense by moving away from the line of attack. However, during fights this type of defense is rarely used. The study found that savate fighters mainly choose defense in the form of moving back (stepping). This approach has obvious disadvantages.Firstly, it allows the opponent to get enough time and space to deliver a powerful blow. Secondly, by increasing the distance during defense by moving back, fighters lose the opportunity to effectively implement their counterattacks.
Keywords: savate; fighter; attacking and counterattacking actions; fight; competitive activity